IMF Stabilization Programs and their Effects on the World Economic Crises - Demiroglu, Tulin; Karagoz, Murat (ELSEVIER SCIENCE BV, 2016)
The aim of this study is that analyzing the relationship between IMF Stabilization Programs and its effect on the experienced world economic crises. The Great Depression and World War I and II faced by the world caused to be deeply shaken of the economies. Eventually, the countries were forced to create barriers against each other to protect the war-damaged economies. The world countries agreed with establishment of IMF to surpass the economic crisis. This article is concentrated on a question is that Whether the IMF stabilization Programs effected positively or triggered into worse situation and crisis the war-damaged economies? The examples crises are Mexican Crisis in 1994, South-eastern Asia Crisis in 1997, Russian Crisis in 1998, Argentina Crisis in 2001 and Turkey Crises in 1994, 2000 and 2001. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: IMF; stabilization programs; economic crises; Business & Economics